Sustainable entrepreneurship in academia: Challenges, strategies, and the roles in university context - Dormido, Yasmin Pascual; Ratnawati, Ratnawati (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
Sustainable entrepreneurship has emerged as a transformative force within higher education, reflecting a growing emphasis on ethical, responsible, and future-oriented business practices. Its integration into academic contexts underscores the critical role universities play in fostering entrepreneurial mindsets that align with sustainable development goals. However, despite its rising prominence, there remains a lack of comprehensive conceptual exploration regarding the role and significance of sustainable entrepreneurship toward challenges in shaping educational approaches and institutional strategies within higher education. Furthermore, this article aims to investigate the interconnected relationship between academia, entrepreneurship, and sustainability by articulating the unique role of universities as pivotal hubs for nurturing sustainable business ideas. It further explores the key challenges and innovative strategies involved in scaling sustainable ventures from academic environments to broader market ecosystems. Additionally, it analyzes the employed mechanisms and approaches universities to fostering ecosystems conducive to and supportive of sustainable academic entrepreneurship, underscoring the importance of promoting innovation, interdisciplinary collaboration, and stakeholder engagement. Finally, the article explores the increasingly pivotal role of technology and innovation in driving the success of sustainable academic ventures, with a particular focus on transformative technologies poised to shape the future of sustainable business. Through a rigorous conceptual synthesis, this article endeavors to provide valuable insights and an analytical framework for scholars, educators, policymakers, and practitioners vested in advancing sustainable business education and research.